Poly-Phthalocyanine–Doped Graphene Oxide Nanosheet Conjugates for Electrocatalytic Oxidation of Drug Residues - Chundu, Prince; Dube, Edith; Zinyama, Ngceboyakwethu P.; Moyo, Mambo; Shumba, Munyaradzi (Frontiers in Chemistry, 2021)
Donor and acceptor phthalocyanine molecules were copolymerized and linked to graphene oxide nanosheets through amidation to yield electrocatalytic platforms on glassy carbon electrodes. The platforms were characterized , TEM, SEM, FTIR, UV/VIS spectroscopy, cyclic voltammetry and electrochemical impedance spectroscopy. The fabricated electrochemical catalytic surfaces were then evaluated towards electrocatalytic detection of ascorbic acid and tryptophan. These were characterized by a wide linear dynamic range, low limits of detection and quantification of 2.13 µM and 7.12 µM for ascorbic acid and 1.65 µM and 5.5 µM for tryptophan respectively. The catalytic rate constant was 18.6 M-1s-1 and 15.1 M-1s-1 for ascorbic acid and tryptophan respectively. Gibbs energy for the catalytic reactions were -17.45 kJ mol-1 and -14.83 kJ mol-1 depicting a spontaneous reaction on the electrode surface. The sensor platform showed an impressive recovery in waste fresh cow milk in the range 91.71% – 106.73% for both samples. The developed sensor therefore shows high potential for applicability for minute quantities of the analytes in real biological samples.